Variability of nitrogen use efficiency by foxtail millet cultivars at the seedling stage - Erying, Chen; Ling, Qin; Yanbing, Yang; Huawen, Zhang; Hailian, Wang; Bin, Liu; Shuting, Yu; Runfeng, Wang; Yanan, Guan (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to identify the genetic variation of foxtail millet (Setaria italica) cultivars, from three ecogeographic origins in China, regarding the uptake and utilization of N by the genotypes at the seedling stage, aiming at the genetic improvement of this crop. Seedlings of 79 cultivars were fertilized with a nutrient solution, on a sand substrate, and evaluated under low-N (LN, 0.2 mmol L-1) and high-N (HN, 6.0 mmol L-1) concentrations. A large variation was observed between cultivars, among the three ecogeographic regions, for shoot biomass, shoot N content and concentration, and N use efficiency (NUE), uptake efficiency (NupE), and utilization efficiency (NutE), especially under HN conditions. Cultivars of Northwest China showed the highest variation for shoot biomass, N content, NUE, and NupE. A strong positive correlation was observed between NUE and NupE, and NUE and NutE, but there was no correlation between NupE and NutE. NupE accounted for 77.6% of the total variation of NUE, and NutE for the rest. The uptake and utilization of N show a large variation among the foxtail millet cultivars at the seedling stage, and the variation of N uptake contributes more than that of N utilization to the variation of N use efficiency.